Skuteczność i efektywność certyfikacji systemów zarządzania jakością w przedsiębiorstwie - Witkowski, Jarosław; Baraniecka, Anna (Effectiveness and Efficiency of Quality Management Systems Certification in an Enterprise, 2006)
The paper deals with the main problems in evaluating the effectiveness and the efficiency of the quality management systems ISO 9001:2000. The authors argue that a high cost as wells as a time consuming quality assurance system implementation is not always effective and efficient. The case study of the quality management system of Polish paper machinery producer is presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 390-400